The impact of staging FDG-PET/CT on treatment for stage III NSCLC - an analysis of population-based data from Ontario, Canada - Beers, Craig A.; Pond, Gregory R.; Wright, James R.; Tsakiridis, Theodoros; Okawara, Gordon S.; Swaminath, Anand (Frontiers in Oncology, 2023)
Fluoro-2-deoxyglucose positron-emission tomography (FDG-PET/CT) is now considered a standard investigation for the staging of new cases of stage III NSCLC. However, there is not published level 3 evidence demonstrating the impact of FDG-PET/CT on appropriate therapy in this setting. Using retrospective population-based data, we sought to examine the role and timing that FDG-PET/CT scans play in influencing treatment choice, as well as survival in patients diagnosed with stage III NSCLC.A retrospective cohort of patients diagnosed with stage III NSCLC from 2009-2017 in Ontario were identified from the IC/ES (formerly Institute of Clinical Evaluative Sciences) database. FDG-PET/CT utilization over time, trends in mediastinal biopsy technique and usage, the impact of FDG-PET/CT on overall survival (OS), and its influence on use of concurrent chemoradiotherapy (CRT) were explored. The impact of timing of pre-treatment FDG-PET/CT on OS was also analyzed (≤28 days prior to treatment, 29-56 days prior, and >56 days prior).Between 2007 and 2017, a total of 13 796 people were diagnosed with stage III NSCLC in Ontario. FDG-PET/CT utilization increased over time with 0% of cases in 2007 and 74% in 2017 with pretreatment FDG-PET/CT scans. The number of patients who received a mediastinal biopsy similarly increased in this timeframe increasing from 41% to 53%. More patients with pre-treatment FDG-PET/CT scans received curative-intent therapy than those who did not: 23% vs 13% for CRT (p<0.001), and 23% vs 10% for surgery (p<0.001). Median OS was longer in those with FDG-PET/CT scans prior to treatment (17 vs 11 months), as was 5-year survival (22% vs 14%, p<0.001), and this held true on both univariate and multivariate analyses. Timing of FDG-PET/CT scan relative to treatment was not associated with differences in OS.Improvements in OS were seen in this cohort of stage III NSCLC patients who underwent a pretreatment FDG-PET/CT scan. This can likely be attributed to stage-appropriate therapy due to more complete staging using FDG-PET/CT. This study stresses the importance of complete staging for suspected stage III NSCLC using FDG-PET/CT, and a need for continued advocacy for increased access to FDG-PET/CT scans.